Optimization of Hydropriming Techniques for Cowpea Seed Invigoration - K. KRISHNAKUMARY,; A. VENKATASUBRAMANIAM,; C. MINI, (Seed Research, 2026)
Many presowing treatments are reported to improve seed invigoration in vegetable crops. An investigation was carried out to optimize the hydropriming techniques for vigour enhancement in cowpea (variety Anaswara) seeds by standardizing the durations of priming and volume of water to be used. Highest germination percentage (100), speed of germination (24.9), vigour index-1 (3540) and vigour index-2 (8.8) were observed when the seeds were soaked in double the volume of water for 2 h. Increase in germination and vigour in this treatment was due to the highest initial germination, maximum dry matter production and minimum number of days required for 50 per cent germination. Hydropriming for 8, 16 and 32 h (prolonged soaking) resulted in lower values in almost all the parameters and it can be considered as over priming. This study proved the importance of duration of soaking and volume of water in cowpea seed invigoration.